The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1248/bpb.31.1059
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-Like Vesicles with Dipeptidyl Peptidase IV in Human Saliva

Abstract: During the last decade, a novel mechanism of protein release has been recognized that involves small (30-100 nm) membrane vesicles termed exosomes. [1][2][3] Exosomal vesicles are secreted following the fusion of multivesicular late endosomes with the plasma membrane. While the range of exosomal proteins depends on cell type, these vesicles commonly carry cell-surface proteins and cytoskeletal proteins. Several physiologic roles have been assigned to exosomes, including the expulsion of obsolete membrane const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
178
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(185 citation statements)
references
References 38 publications
6
178
0
1
Order By: Relevance
“…The findings presented here are novel for gal-3 and gal-8, since no literature data regarding their presence in EVs of trophoblast origin have been reported so far. However, both gal-3 and gal-8 were found in EVs from different cell types or body fluids (Ogawa et al, 2008;Wang et al, 2012;Webber et al, 2014;Hurwitz et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The findings presented here are novel for gal-3 and gal-8, since no literature data regarding their presence in EVs of trophoblast origin have been reported so far. However, both gal-3 and gal-8 were found in EVs from different cell types or body fluids (Ogawa et al, 2008;Wang et al, 2012;Webber et al, 2014;Hurwitz et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, in addition to immune cells, many other cell types have been described as exosome secretory cells such as epithelial cells, 19 neurons 20 and tumor cells. 21 Exosomes can be isolated from cell culture supernatants and can be found in numerous body fluids such as blood, 22,23 urine, 24 saliva, 25 bronchoalveolar fluid, 26 seminal fluid, 27 amniotic fluid, 28 breast milk, 29 tumor effusions 30 and cerebrospinal fluid. 31 …”
Section: Discovery Of Exosomesmentioning
confidence: 99%
“…Another research article demonstrates the presence of exosome-like vesicles with dipeptidyl peptidase (DPP) IV activity in human saliva . Ogawa et al (2008) demonstrated that the DPP IV was able to cleave substance P and glucose-dependent insulinotropic polypeptide .…”
Section: Peptidase and Protease Activity And Their Presence In Salivamentioning
confidence: 99%